Human resource development at headquarters of vietnam bank for agriculture and rural development- Hung Yen branch - Nguyễn, Đức Long (2020)
The thesis has suggested several aspects: Overview of research activities and theoretical foundations of human resources development. Human resources development situation at Agribank Headquarter - Hung Yen Branch, Human resources development solutions at Agribank Headquarter - Hung Yen Branch with 5 main solutions as belo, Human resources development planning and planning solutions, Solutions for recruiting human resources, The arrangement of human resources solutions, Solutions for training and professional training to improve the quality of human resources, Solutions to perfect mechanisms and policies to encourage the development of human resources